2022
DOI: 10.32598/jpr.10.specialissue.584.3
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Diabetes in Children: A Narrative Review

Mahin Hashemipour

Abstract: Background: COVID-19 is an unknown and novel virus that creates a challenge with all comorbid conditions, including diabetes mellitus (DM). Although DM has not been determined as a definite risk factor for COVID-19 in childhood, clinicians should consider the potential association between DM and COVID-19. Objectives: This study aimed to review COVID-19 and DM comorbidity in children. Methods: ISI Web of Science, PubMed, and Google Scholar were investigated to find relevant articles regarding COVID-19 and DM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The clinical characteristics of COVID-19 are categorized into five distinct types as follows (5) (6).…”
Section: Covid-19mentioning
confidence: 99%
“…The clinical characteristics of COVID-19 are categorized into five distinct types as follows (5) (6).…”
Section: Covid-19mentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID- 19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, has resulted in lung failure and the need for mechanical ventilation (1)(2)(3). Initially, during the early stages of the COVID-19 pandemic, the incidence of positive cases among children was deemed negligible, and it was assumed that children were less susceptible (4)(5)(6). However, subsequent studies have indicated that children and adolescents are also vulnerable to SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%